Functional Characterization and Crystal Structure of the Type II Peptidyl Carrier Protein ColA1a in Collismycins Biosynthesis†. Issue 9 (25th May 2020) - Ma, Xueyang; Wang, Guiyang; Liu, Tan; Chi, Changbiao; Zhang, Zhongyi; Yang, Donghui; Liu, Wen; Ma, Ming
Abstract : Summary of main observation and conclusion: Collismycins (COLs) are antibiotics characterized by a 2, 2′‐bipyridine (2, 2′‐BP) core composed of a trisubstituted ring A and an unmodified ring B. The 2, 2′‐BP core, which possesses metal‐chelating ability and plays key roles in various biological activities of COLs, is biosynthesized by a nonribosomal peptide synthetase (NRPS)‐polyketide synthase (PKS) hybrid machinery. The starter module of the NRPS‐PKS hybrid machinery consists of a type II peptidyl carrier protein (PCP) ColA1a and an adenylation protein ColA1b. We here report the functional characterization of ColA1a and ColA1b in vitro, confirming their functions in selection and loading of picolinic acid (PA), instead of normal amino acid substrates, as the origin of ring B in COLs. The 2.1 Å crystal structure of ColA1a was solved, revealing structural features including the additional helices α1a, α1b and missing helix α3, which may reflect unique interactions of ColA1a with other NRPS‐PKS proteins/domains or substrate. Primary and tertiary structural comparison of ColA1a with other PCPs revealed the structural basis for their typical α‐helical bundle, providing a better understanding of the structural flexibility of PCPs. These results facilitate the starter module engineering for the generation of COL derivatives with ring B modifications in the future.